Pemberdayaan Kelompok Ibu-Ibu PKK Desa Babakan, Kecamatan Darmaga, Kabupaten Bogor dalam Upaya Swamedikasi Menggunakan Tanaman Obat - Siti Sa’diah; Katrin Roosita; Rudi Heryanto (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2015)
Looking by the lack of information about medicinal plants and not good enough effort by the member of PKK in optimizing swamedication with medicinal plants, IbM held three types of training about swamedication using medicinal plants and monitoring the program. The purpose of this program is to improve the skills and knowledge of every member of PKK about medicial plants, grow the plants at limited space and gain the benefits from medicinal plants for inhabitant. The first training was about improving knowledge about medicinal plants and distribute seedling of medicinal plants which can plant at house yards. The second training was about production techniques of fourinds traditional medicine: jamu beras kencur, kunyit asam, galohgor and instant type of beras kencur. The last training was about techniques for organic compost from household waste. Process of evaluating and monitoring held after all the training done, then there was interview session and held a competition of producing jamu. The evaluation shows there was some improvement in consumption of beras kencur and kunyit asam families and inhabitant. Also, there was indication of transferred information from aenoughtrained member to not-trained member in informal ways. Overall, all of the programs has done with good achievement. This programs already made a significant improvement in public information about medicinal plants.